Immigrants in the Grand Duchy of Luxembourg and Its Public Security - Paweł Olbrycht (Historia i Polityka, 2021)
The Grand Duchy of Luxembourg is one of the smallest European countries – both in terms of area and population. As in the case of the so-called European micro-states (with less than 500,000 inhabitants – Luxembourg alone has slightly more), it is characterized by a high economic level, especially the living standards of its inhabitants.